Application and prospect of intelligent voice technology in the field of agricultural machinery - Xu, Xue-ming; Wang, Lin; Zhang, An-qi; An, Xiao-fei; Wang, Hao; Zhu, Xiao-yu (Frontiers in Plant Science, 2025)
With the development of smart agricultural machinery technology, the application of intelligent voice technology in smart agricultural machinery is becoming increasingly widespread. As a new interactive method, intelligent voice technology can reduce operator workload, improve operational quality, and enhance operational safety in agricultural machinery. This article reviews the current state of development of intelligent voice technology in agriculture, summarizing the bottlenecks and challenges in its application within the agricultural machinery field. It further proposes a framework for intelligent voice technology in agricultural machinery and presents technical implementation plans for two typical application scenarios: intelligent control and fault diagnosis/early warning of agricultural machinery. These findings aim to provide a reference for the application of intelligent voice technology in the agricultural machinery sector. Finally, development suggestions are proposed, including building specialized voice recognition vocabularies and semantic parsing models, exploring the application of artificial intelligence in agricultural machinery voice technology, and establishing relevant technical standards for intelligent voice applications in agricultural machinery. This article provides important references and insightful ideas for the development of intelligent voice technology in the agricultural machinery field, which will facilitate the promotion and adoption of intelligent agricultural machinery technologies.